TRADITIONAL GOAT PRODUCTION AND INCOME GENERATION OF GOAT FARMERS IN ZANGON-KATAF LOCAL GOVERNMENT AREA OF KADUNA STATE, NIGERIA - Kaine, A. I. N.; Ajeiigbe, E. A.; Ogbonna, S. I. (Journal of Agripreneurship and Sustainable Development, 2021)
The study was conducted in Zangon-Kataf Local Government Area of Kaduna State, Nigeria. Multi-stage random sampling procedure was used to select 50 farmers used for the study. Structured questionnaire was used to collect data required for the study. Data collected were analyzed using qualitative and quantitative techniques. The result established that goat farmers in the study area were relatively young with a mean age of 38 years. Literacy level and household size were high. Enterprise variables established that the farmers were experienced and that goat production was an income generating enterprise with positive net profit and a mean net income of N2,719.00, that is, 7.769 at N350 per doller. Return on investment (ROI) was established to be positive with a value 0.13 implying that goat production in the study area was profitable. The constraints to goat production in the study area were poor road network, pest and diseases, among others. It was recommended that, campaign and sensitization of the profitability of goat production should be carried out. Also, non-governmental organizations, government and financial institutions should assist goat producers by providing funds in form of soft loan, credit facilities and needed capital to improve their financial base and increase their production capability.